Peran Nefroprotektif Pentoxifylline Terhadap Ekspresi TGF-β1, Kolagen Tipe-4, MMP-9, Glomerulosklerosis serta Albuminuria pada Mencit Galur Swiss Setelah Diinduksi Doksorubisin - Bambang Purwanto (MEDIA MEDIKA INDONESIANA, 2010)
Nephroprotective effect of pentoxifylline through improvement in the expression of TGF-β1, type-IV collagen, MMP-9, glomerulosclerosis and albuminuria in swiss strain mice after inducing by doxorubicinBackground: Nephrotoxic effects of doxorubicin (DXR) as a cancer drug is still a problem. Pentoxifylline (PTX) has the nephrotoxic effects. The combination of DXR and PTX might reduce the nephrotoxic effects of DXR. The aim of study was to prove the nephroprotective effect of PTX on DXR nephrotoxicity through the improvement of TGF-β1, type-4 collagen, MMP-9, as well as the levels of glomerulosclerosis and albuminuria.Method: Fourty-four males Swiss strain mice, divided into three groups as control group (C) injected with NaCl 0.9%; DXR induced nephrotoxicity (D); and effect of PTX on D (P/D) by intraperitoneally, respectivelly, each group consisted of 8 mice. Injections done once a week for three consecutive weeks. At the 4th and 8th weeks post-treatment, all eight mice of each group were sacrificed. Examination of TGF-β1, type-4 collagen, and MMP-9 expression was done by immunohistochemistry with monoclonal antibody. Glomerulosclerosis examination was done by a histopathologist, using VvG staining. While albuminuria examination was done by Elisa. The statistic was investigated using one-way ANOVA.Result: In the fourth week proteins expression was increased from C to D and subsequently decreased in P/D for TGF-β1, collagen type-IV, glomerulosclerosis and albuminuria. Otherwise MMP-9 expression was increased from C to D and in P/D. While in the eighth week proteins expression was increased from C to D and subsequently decreased in P/D for TGF-β1, collagen type-IV, glomerulosclerosis, and albuminuria. Otherwise MMP-9 expression was decreased from C to D and subsequently increased in P/D.Conclusion: The combination of PTX and DXR can reduce the nephrotoxic effects of DXR. PTX was proved to be nephroprotector inducing by DXR.ABSTRAKLatar belakang: Efek nefrotoksik doxorubicin (DXR) sebagai obat kanker masih menjadi masalah. Pentoxifylline (PTX) memiliki efek nefroprotektif. Kombinasi DXR dan PTX diharapkan untuk mengurangi efek nefrotoksik DXR. Tujuan penelitian ini adalah menjelaskan perbedaan ekspresi TGF-β1, kolagen tipe-IV, MMP-9, serta tingkat glomerulosklerosis dan albuminuria dalam keadaan normal, nefrotoksik dan nefroprotektif.Metode: Mencit strain Swiss jantan 48 ekor, secara acak dibagi tiga kelompok dengan setiap kelompok 16 ekor. Masing-masing kelompok diberikan intraperitoneal sekali seminggu selama tiga minggu berturut-turut 0,2 ml NaCl 0,9% pada kelompok kontrol (C); 0,038 mg DXR/20 g berat badan untuk kelompok nefrotoksik (D); serta dosis kombinasi 0,038 mg DXR/20 g berat badan dan 1,6 mg PTX/20 g berat badan untuk kelompok terapi (P/D). Pada minggu ke-4 dan 8 setelah pengobatan, 8 mencit masing-masing kelompok dikorbankan untuk pengumpulan sampel. Ekspresi TGF-β1, kolagen tipe-IV dan MMP-9 dinilai dengan immunohistokimia. Glomerulosklerosis dinilai secara histopatologis, menggunakan pewarnaan VvG. Sementara albuminuria dinilai dengan teknik Elisa. Statistik dianalisis menggunakan one-way ANOVA. Hasil: Pada minggu keempat terlihat ekspresi meningkat dari C ke D dan kemudian menurun pada P/D untuk TGF-β1, kolagen type-IV, glomerulosklerosis dan albuminuria. Sebaliknya ekspresi MMP-9 meningkat dari C ke D dan pada P/D. Pada minggu ke delapan terlihat ekspresi meningkat dari C ke D dan kemudian menurun pada P/D untuk TGF-β1, kolagen type-IV, glomerulosklerosis, dan albuminuria. Sebaliknya ekspresi MMP-9 menurun dari C ke D dan selanjutnya meningkat pada P/D.Simpulan: Penggunaan kombinasi PTX dan DXR dapat mengurangi efek nefrotoksik dari DXR.